Pelatihan Penulisan Puisi untuk Siswa SMP Muhammadiyah Rappang dengan Pendekatan Ekspresif - Anita Candra Dewi; Sutarsi Suhaeb; Mantasia Mantasia; Saharuddin Saharuddin; Ninik Rahayu Ashadi (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The ability to write poetry is an important part of learning Indonesian language and literature because it supports the development of self-expression, creativity, and language skills. However, in reality, many junior high school students still have difficulty expressing their ideas and feelings in the form of communicative and meaningful poetry. This community service activity aims to provide poetry writing training to students of Muhammadiyah Rappang Junior High School through an expressive approach. This approach emphasizes students' freedom to express their thoughts, emotions, and personal experiences into poetry. The method of implementing the activity includes counseling, poetry writing practice, and joint reflection. The results of the training showed an increase in students' interest and ability in writing poetry. Students become more confident in expressing inner experiences through more varied diction, imagery, and language styles. In addition, the expressive approach encourages an inclusive and participatory learning atmosphere. Thus, this training not only improves poetry writing skills, but also builds students' emotional and aesthetic awareness. This activity is expected to be a model of literacy activities that can be applied in other schools in order to strengthen character education and artistic expression.